PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATA KULIAH KEWIRAUSAHAAN PROGRAM STUDI PENDIDIKAN KESEJAHTERAAN KELUARGA UNIVERSITAS NEGERI PADANG - Karmila, Melsah; Yulastri, Asmar; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
This study aims at developing interactive multimedia valid and practical in entrepreneurship courses and analyze the validity and practicalities of multimedia are developed. This research is a development model that IDI consists of three stages: define (determine), develop (development) and Evaluate (ratings). Subjects consisted of 4 validator, 30 students to test the practicalities. The technique of collecting data using questionnaires and analyzed with the formula Aiken's V for validity analysis and descriptive analysis using a percentage formula for analysis practicalities. The results showed that the value of design validation 0.83 with valid category and validation of the contents of 0.83 with a valid category. Test the practicalities of the two lecturers, obtained an average score of 83.85% with a very practical category. Test the practicalities of the students obtained an average score of 83.03% with a very practical category. Based on the above it can be concluded that interactive multimedia is valid and very practical for use as a medium of learning in the Family Welfare Education courses State University of Padang.Keywords: development, multimedia, interactive, entrepreneurship